Financial literacy and the impact of movement control order (MCO) among the Muslim mompreneurs: a qualitative study - Mohd Yusoff, Syarah Syahira (Research Centre for Islamic Economics (IKAM), 2021)
This empirical paper investigates how the mompreneurs manage their businesses during the Covid-19 lockdown and how the pandemic affects their family. The role of a mother in a family encompasses the livelihood of the family members, which extends to the family’s financial standing. A mother’s role in a family ranges from a homemaker and, to a certain extent, a financial provider. In Malaysia, it was reported in 2018 that 60.2% of entrepreneurs are housewives. However, it is believed that many women are working at and from home with high cost of living, especially in urban areas. They become home-based entrepreneurs, especially during this unprecedented pandemic, i.e. Covid-19, and restricted by the Movement Control Order (MCO). This study adopted an exploratory qualitative study whereby six (6) mompreneurs who are operating their businesses from home were interviewed to understand how the pandemic and the lockdown have affected their lives. This paper further examines their coping mechanism to the pandemic and financial income during this crisis. Mompreneurs’ financial literacy is also observed in this paper to explore their financial understanding. This research is an exploratory study, and it only provides general ideas on how a home-based businesswoman survive and cope during the lockdown. The findings from this paper are suitable to be used as a benchmark for an extensive quantitative study in the future to further understand the behaviour of the mompreneurs, especially in Malaysia.